A novel shuttle-like Fe3O4–Co3O4 self-assembling architecture with highly reversible lithium storage1. Issue 86 (18th September 2015) - Shang, Kaina; Li, Wentao; Liu, Yongmei; Zhang, Wenguang; Yang, Hui; Xie, Jiqing; Liu, Zuyan; Chou, Shu-Lei; Zhao, Lingzhi; Zeng, Ronghua
<x xml:space="preserve">Abstract</x> An unprecedented shuttle-like Fe3O4–Co3O4 self-assembling architecture is obtained through a facile hydrothermal method. Obviously, the electrochemical performance of the obtained composite is large enhanced in comparison with that of pristine Co3O4.